2016
DOI: 10.1038/nm.4075
|View full text |Cite|
|
Sign up to set email alerts
|

Nod2-mediated recognition of the microbiota is critical for mucosal adjuvant activity of cholera toxin

Abstract: Cholera toxin (CT) is a potent adjuvant for inducing mucosal immune responses. However, the mechanism by which CT induces adjuvant activity remains unclear. Here we show that the microbiota is critical for inducing antigen-specific IgG production after intranasal immunization. After mucosal vaccination with CT, both antibiotic-treated mice and germ-free (GF) had reduced antigen-specific IgG, recall-stimulated cytokine responses, an impaired follicular helper T (TFH) response and reduced plasma cells. Recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 53 publications
5
92
0
1
Order By: Relevance
“…CT has been known as a potent mucosal immunogen and adjuvant for several decades; we confirm and extend a recent report linking these CT properties with the intestinal microbiota 14 . With SFB as a known stimulator of endogenous Th17 cells in the intestine, we found that in addition, other commensal bacteria such as those belonging to the altered Schaedler flora, can also participate in the regulation of intestinal Th17 and antibody responses to CT mucosal immunization.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…CT has been known as a potent mucosal immunogen and adjuvant for several decades; we confirm and extend a recent report linking these CT properties with the intestinal microbiota 14 . With SFB as a known stimulator of endogenous Th17 cells in the intestine, we found that in addition, other commensal bacteria such as those belonging to the altered Schaedler flora, can also participate in the regulation of intestinal Th17 and antibody responses to CT mucosal immunization.…”
Section: Discussionsupporting
confidence: 89%
“…Mucosal delivery of CT induces strong mucosal and systemic humoral immune responses to itself and co-administered protein antigens 12 , but does not cause intestinal inflammation. CT does so by activating Gsα and the nucleotide-binding oligomerization domain containing 2 (Nod2) expressed in CD11c + cells 13,14 . Th17 cells can convert into T follicular helper (Tfh) cells in the PPs, thus enhancing high-affinity intestinal IgA production 15 , suggesting an important role of Th17 cells in the induction of antigen-specific IgA in the gut, which in turn is involved in the protection against microbial antigens at the mucosal surface 16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, higher titers of serum IgG against fecal symbiotic bacteria were frequently reported in patients with either Crohn’s disease or Colitis, which was thought to reflect either prior infections or systemic translocation of gut bacteria in these patients due to “leaky” epithelial barrier (126). In addition, we recently reported that gut symbiotic bacteria promote the adjuvant activity of cholera toxin, an enterotoxin secreted by Vibrio cholera that has been used as a potent mucosal adjuvant, through Nod2-mediated recognition of its microbial agonist by dendritic cells (127). …”
Section: Regulation Of B Cell Immune Response By the Gut Microbiotamentioning
confidence: 99%
“…2/2 mice were obtained from Dr. J.-P. Hugot (Hôpital Robert Debré, Université Paris Diderot, Paris, France) (14), Villin-Cre (B6.Cg-Tg(Vil-cre) 997Gum/J) and LyzM-Cre (B6.129P2-Lyz2 tm1(cre)Ifo /J) mice were purchased from The Jackson Laboratory (Bar Harbor, ME), and NOD2 flox/flox mice were obtained from Dr. P. Rosenstiel (Institute for Clinical Molecular Biology, Christian-Albrechts-University, Kiel, Germany) (15). NOD2 flox/flox mice were generated by genOway (Lyon, France).…”
Section: Nod2mentioning
confidence: 99%